Frequency and reactivity of antigen-specific T cells were concurrently measured through the combination of artificial antigen-presenting cell, MACS and ELISPOT. Issue 1 (December 2017) - Shen, Chuanlai; Xu, Tao; Wu, You; Li, Xiaoe; Xia, Lingzhi; Wang, Wei; Shahzad, Khawar; Zhang, Lei; Wan, Xin; Qiu, Jie
Abstract Conventional peptide-major histocompatibility complex (pMHC) multimer staining, intracellular cytokine staining, and enzyme-linked immunospot (ELISPOT) assay cannot concurrently determine the frequency and reactivity of antigen-specific T cells (AST) in a single assay. In this report, pMHC multimer, magnetic-activated cell sorting (MACS), and ELISPOT techniques have been integrated into a micro well by coupling pMHC multimers onto cell-sized magnetic beads to characterize AST cell populations in a 96-well microplate which pre-coated with cytokine-capture antibodies. This method, termed AAPC-microplate, allows the enumeration and local cytokine production of AST cells in a single assay without using flow cytometry or fluorescence intensity scanning, thus will be widely applicable. Here, ovalbumin257–264 -specific CD8+ T cells from OT-1 T cell receptor (TCR) transgenic mice were measured. The methodological accuracy, specificity, reproducibility, and sensitivity in enumerating AST cells compared well with conventional pMHC multimer staining. Furthermore, the AAPC-microplate was applied to detect the frequency and reactivity of Hepatitis B virus (HBV) core antigen18–27 - and surface antigen183–191 -specific CD8+ T cells for the patients, and was compared with conventional method. This method without the need of high-end instruments may facilitate the routine analysis of patient-specific cellular immune response pattern to a given antigen in translational studies.